The ABCC6 transporter: what lessons can be learnt from other ATP-binding cassette transporters? - Vanakker, Olivier M.; Hosen, Mohammad J.; De Paepe, Anne (Frontiers in Genetics, 2013)
ABC transporters represent a large family of ATP-driven transmembrane transporters involved in uni- or bidirectional transfer of a variety of substrates. Divided in 7 families, they represent 48 transporter proteins, several of which are associated with human disease. Among the latter is ABCC6, a unidirectional exporter protein primarily expressed in liver and kidney. ABCC6 deficiency causes pseudoxanthoma elasticum (PXE), characterised by calcification and fragmentation of elastic fibres, resulting in oculocutaneous and cardiovascular symptoms. Unique among connective tissue disorders, the relation between the ABCC6 transporter and ectopic mineralization in PXE remains enigmatic, not in the least because of lack of knowledge on the substrate(s) of ABCC6 and its unusual expression pattern. Because many features, including structure and transport mechanism, are shared by ABC transporters, it is worthwhile to evaluate if and to what extent the knowledge on the (patho)physiology of other transporters may provide useful clues towards understanding the (patho)physiological role of ABCC6. In this paper, we summarize relevant knowledge and methods for analysis on ABC transporters which may be useful for the further study of ABCC6.